2002
DOI: 10.4067/s0718-19572002000100007
|View full text |Cite
|
Sign up to set email alerts
|

Variación temporal del fitoplancton entre 1993 y 1998 en una estación fija del seno Aysén, Chile (45º26'S 73º00'W)

Abstract: Variación temporal del fitoplancton entre 1993 y 1998 en una estación fija del seno Aysén, Chile (45º26′S 73º00′W)Temporal change of the phytoplankton between 1993 and 1998 in a fixed station inside Aysén fjord, Chile (45º26′S 73º00′W)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
1
14
0
1
Order By: Relevance
“…D. acuminata was the most abundant species, whereas D. acuta, D. caudata, and D. rotundata were scarce throughout the entire study period. This coincided with observations from Muñ oz et al (1992) and Cassis et al (2002) in Aysé n Fjord (45826 0 S-73800 0 W, southern Chile), who found greater concentrations of D. acuminata and D. acuta than the others Dinophysis.…”
Section: Seasonal Variabilitysupporting
confidence: 91%
See 3 more Smart Citations
“…D. acuminata was the most abundant species, whereas D. acuta, D. caudata, and D. rotundata were scarce throughout the entire study period. This coincided with observations from Muñ oz et al (1992) and Cassis et al (2002) in Aysé n Fjord (45826 0 S-73800 0 W, southern Chile), who found greater concentrations of D. acuminata and D. acuta than the others Dinophysis.…”
Section: Seasonal Variabilitysupporting
confidence: 91%
“…Several species of the Dinophysis that tend to represent a small percentage (1-10%) of the microplanktonic community are regular components of the planktonic flora from the Chilean Southern Canals (Muñ oz et al, 1992;Uribe et al, 2001;Cassis et al, 2002). D. acuta Ehrenberg and D. acuminata Claparede & Lachmann are the most frequent and abundant species (Muñ oz et al, 1992;Cassis et al, 2002), while D. fortti Pavillard and D. hastata Stein, are rarely observed and lower densities in Aysé n Fjord (44.88S) (Muñ oz et al, 1992;Cassis et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain species are able to completely dominate a phytoplankton community (Legrand et al, 2003). In Chilean fjords ecosystems, diatoms are known to represent a significant component of the overall phytoplankton biomass (Iriarte et al, 2001;Cassis et al, 2002;Alves-de-Souza et al, 2008;Iriarte & González, 2008). In addition to efficiently transferring energy to higher trophic levels, diatoms make a significant contribution to the downward transfer of organic carbon (Iriarte et al, 2007;González et al, 2010;Montero et al, 2011;Iriarte et al 2013).…”
Section: __________________mentioning
confidence: 99%